Molecular phylogeny and taxonomic revision of Coleosporiaceae (Pucciniales): the genera Quasipucciniastrum and Aculeastrum reassessed and a new combination proposed - Malysheva, Vera; Dudka, Vasiliy (Phytotaxa, 2025)
Two genera of rust fungi, Quasipucciniastrum and Aculeastrum, have recently been described within the family Coleosporiaceae. However, their taxonomic status as separate, independent genera remained a matter of debate. In the present study, we investigated the taxonomy of Quasipucciniastrum and Aculeastrum using morphological and molecular (nuc rDNA 5.8S-ITS2 [ITS barcode] and partial nuc 28S rDNA D1–D3 regions [28S]) data, including a detailed study of the type collections of Pucciniastrum potentillae and Thekopsora agrimoniae. Based on type specimen examination, Asian species Q. potentillae is considered synonym of Q. ochraceum. Furthermore, as the main outcome of our phylogenetic study, we synonymize Quasipucciniastrum and Aculeastum with the genus Thekopsora, and propose a new nomenclatural combination Thekopsora arctica.